2017
DOI: 10.1021/acs.inorgchem.6b02770
|View full text |Cite
|
Sign up to set email alerts
|

Driving Forces in the Sharpless Epoxidation Reaction: A Coupled AIMD/QTAIM Study

Abstract: In order to better understand the epoxide-formation step of the Sharpless epoxidation process, a set of 263 oxygen-transfer reactions reflecting the complexity of the Sharpless epoxidation process were studied using density functional theory (DFT) and Bader's quantum theory of atoms in molecules (QTAIM). The diversity within these reactions reflects the different ligands in the coordination sphere of vanadium and also different substrates (alkene and an allylic alcohol both free and in the form of an alcoxo li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…The relatively large dispersion of E Mol /n electrons shown in Figure 5a is justifiable by the relatively small impact the iVSCC should have on the potential felt by the electrons in the atomic basins pertaining to the ligands of each TM complex. Although relying on a local adherence to the virial theorem, the negative value of the electronic kinetic energy in the metal basin, −K(M), is a suitable surrogate for contribution of the metal's population to the electronic energy of the molecule, specially when considering general trends in the data 30,40 .…”
Section: Resultsmentioning
confidence: 99%
“…The relatively large dispersion of E Mol /n electrons shown in Figure 5a is justifiable by the relatively small impact the iVSCC should have on the potential felt by the electrons in the atomic basins pertaining to the ligands of each TM complex. Although relying on a local adherence to the virial theorem, the negative value of the electronic kinetic energy in the metal basin, −K(M), is a suitable surrogate for contribution of the metal's population to the electronic energy of the molecule, specially when considering general trends in the data 30,40 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure depicts the TS for the oxygen-transfer reaction between VO­(O 2 )­(OH) and two olefinic substrates: an alkene (Figure a), and an allylic alcohol (Figure b), together with a representation of the atomic motions associated with the reaction coordinate (i.e., the vibrational mode associated with an imaginary wavenumber), hereafter referred to by ξ. These structures were obtained from a previous study concerning the Sharpless epoxidation process, using the X3LYP functional in conjunction with a mixed basis set of triple-ζ quality. , The vibrational analysis of these TS structures focused on the characterization of the atomic motions along ξ. For this purpose, the lengths for the V–O (3) , V–O (4) , O (3) –O (4) , O (3) –C (7) , and O (3) –C (8) were considered in addition to the internal coordinates generated from the rules explained in the Methodology section.…”
Section: Resultsmentioning
confidence: 99%
“…The fourth and fifth study cases under reported in this work explored the application of VMARD as a way to characterize the motion along the reaction coordinate of the oxygen-transfer step in vanadium-catalyzed epoxidations, and also on different aza-Diels–Alder condensations. Both these studies relied on the data generated in previous studies by the authors. , …”
Section: Computational Detailsmentioning
confidence: 99%
“…This method of wave function analysis enables the recovery of important chemical concepts, such as atoms, functional groups, atomic charges, and bond orders from either electronic structure calculations or X-ray experiments [ 44 ]. Consequently, QTAIM has been applied in the study of a wide variety of chemical and physical problems, such as the examination of different bonds [ 45 , 46 ], adsorption [ 47 , 48 , 49 ], electrical conductivity [ 50 , 51 , 52 ], and catalysis [ 53 , 54 , 55 ].…”
Section: Theoretical Frameworkmentioning
confidence: 99%